21st Century Skills and Character Education: Building Indonesia's Future-Ready Generation - Okki Dwi Cahya; Siti Meliyani (Yayasan Cerdas Pedia Indonesia, 2025)
This systematic literature review examines the integration of 21st century skills and character education within Indonesia's educational framework, addressing the critical need for educational transformation to achieve the Golden Indonesia 2045 vision. The study analyzes the theoretical foundations, implementation challenges, and strategic approaches for developing future-ready competencies among Indonesian students through a comprehensive review of scholarly articles and policy documents from the Scopus database. The research methodology involved systematic collection and analysis of empirical studies, policy documents, and educational frameworks, with particular focus on the Merdeka Curriculum and Profil Pelajar Pancasila (Pancasila Student Profile) implementation. Key findings reveal that while Indonesia has established innovative policy frameworks integrating global competencies with local Pancasila values, significant implementation barriers persist, including infrastructure disparities, teacher preparedness challenges, and inadequate assessment systems. The study demonstrates that project-based learning approaches and local wisdom integration show promising results in developing critical thinking, collaboration, and character development. However, PISA 2022 results indicate substantial gaps in creative thinking capabilities, with only 31% of Indonesian students achieving baseline proficiency compared to 78% across OECD countries. The research concludes that successful integration requires sustained investment in teacher professional development, digital equity initiatives, and comprehensive evaluation frameworks that address both cognitive and character development dimensions. These findings provide essential insights for policymakers and educators working toward building Indonesia's future-ready generation equipped with both 21st century competencies and strong moral foundations